Primary Orbital Mucinous Carcinoma in a Human Immunodeficiency Virus (HIV) Patient: A Case Report - Zahra A Markatia; George A Villatoro; Taimur Siddiqui; Debra J Shetlar; Michael T Yen (Journal of Ophthalmology and Advance Research, 2026)
Mucinous carcinoma is a rare malignancy marked by abundant mucin production, typically found in organs like the breast, colon, and ovary, with orbital involvement being exceptionally rare. This case report presents a 55-year-old male with a history of well-controlled Human Immunodeficiency Virus (HIV) infection, oral squamous cell carcinoma, and recurrent papillomas of the conjunctiva and oropharynx, who developed a firm, enlarging mass in the left superomedial anterior orbit. Histopathology after surgical resection confirmed mucinous carcinoma, and full-body imaging ruled out metastasis, but demonstrated an intensely hypermetabolic left lacrimal sac fossa/upper nasolacrimal duct on Positron Emission Tomography (PET) imaging. Although a maxillectomy and post-excision radiation was advised, the patient declined further intervention. This report highlights the importance of ongoing surveillance in immunocompromised patients, as even those adherent with treatment may develop rare and aggressive malignancies. While Human Papillomavirus (HPV) has known oncogenic potential, its role in orbital mucinous carcinoma remains unclear, warranting further investigation.